Understanding Social Structure and Social Relations in Differentiated Learning in Driving School Programs - Martanti, Fitria; Hardati, Puji (Program Studi Tadris IPS Fakultas tarbiyah IAIN Kudus, 2022)
The purpose of this study was to determine the social structure and social relations in differentiated learning and to find out the obstacles in the preparation of student learning profiles in the driving school program. This is one of the interesting things to study because the driving school program is a new program and uses the principle of differentiated learning. This study uses qualitative methods with data collection techniques using interview, documentation and observation techniques. Based on the results of the study, it can be seen that the social structure of the community is mostly underprivileged families and the education of parents is mostly elementary school graduates. The social relations of students from the research results can be seen from student relations both at school and at home. The obstacles in the implementation of the preparation of student learning profiles are the ability of teachers to identify the needs of students is limited, parents are not able to understand the condition of students such as the physical condition of students who encourage students to use aids in the learning process. Another obstacle faced is the lack of implementation of interest aptitude tests to identify problems faced by students, students' academic abilities, and students' potential in various fields. On the other hand, the student learning profile instrument demands complex identification from both teachers and parents.Keywords: Social Structure, Social Relations, Differentiation, Sekolah Penggerak